The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1474-9726.2007.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic assembly of chromatin complexes during cellular senescence: implications for the growth arrest of human melanocytic nevi

Abstract: Summary The retinoblastoma (RB)/p16INK4a pathway regulates senescence of human melanocytes in culture and oncogeneinduced senescence of melanocytic nevi in vivo . This senescence response is likely due to chromatin modifications because RB complexes from senescent melanocytes contain increased levels of histone deacetylase (HDAC) activity and tethered HDAC1. Here we show that HDAC1 is prominently detected in p16 INK4a -positive, senescent intradermal melanocytic nevi but not in proliferating, recurrent nevus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 70 publications
(92 reference statements)
7
80
0
Order By: Relevance
“…INK4A -proficient (501 mel) and p16 INK4A -deficient melanoma cells (WM9 and B16) and that genetic ablation of p16 INK4A in 501 mel cells does not abrogate the senescence growth arrest phenotype in agreement with previous reports (31). Additionally, CDK2 and p27 KIP1 , two other cell cycle regulators deregulated on MITF depletion and involved in cellular senescence (32,33), do not seem as key mediators of MITF siRNA prosenescing effect.…”
Section: Discussionsupporting
confidence: 75%
“…INK4A -proficient (501 mel) and p16 INK4A -deficient melanoma cells (WM9 and B16) and that genetic ablation of p16 INK4A in 501 mel cells does not abrogate the senescence growth arrest phenotype in agreement with previous reports (31). Additionally, CDK2 and p27 KIP1 , two other cell cycle regulators deregulated on MITF depletion and involved in cellular senescence (32,33), do not seem as key mediators of MITF siRNA prosenescing effect.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, Lezhava (2001) What may be the relationship of our findings to the increase in heterochromatin believed to occur during ageing by the results from Narita et al (2003), Lezhava (2001) and others (Bandyopadhyay et al, 2007;Herbig et al, 2006;Jeyapalan et al, 2007;Imai and Kitano, 1998) and also indicated from the increase in HP1α in the lymphocytes of the elderly group observed in this investigation? As described in the Introduction section of this work, recent in vitro and in vivo results support that dephosphorylation of H1 is associated with the maintenance of the H1 subtypes on chromatin or the close association of the H1 subtypes on chromatin and the formation of, or stabilization of condensed structures (Roth and Allis, 1992;Dou et al, 2006).…”
Section: Accepted Manuscript 21mentioning
confidence: 91%
“…The formation of facultative heterochromatin foci (Narita et al, 2003;Bandyopadhyay et al, 2007;Sedivy et al, 2008), which are known as the senescenceassociated heterochromatin foci (SAHF), occurs on each chromosome (Zhang et al, 2007). SAHF contain HP1 proteins, which modulate histone modifications and epigenetic silencing.…”
Section: Persistent Accumulation Of Foci Components At Unrepairable Dsbsmentioning
confidence: 99%